2021
DOI: 10.3390/molecules26164711
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Receptor Substrate 1 Is Involved in the Phycocyanin-Mediated Antineoplastic Function of Non-Small Cell Lung Cancer Cells

Abstract: Phycocyanin, derived from marine algae, is known to have noteworthy antineoplastic properties. However, the underlying mechanism involved in phycocyanin-mediated anti-growth function on non-small cell lung cancer (NSCLC) cells is still ambiguous. Here, we investigated the mechanism of action of phycocyanin on H1299, A549, and LTEP-a2 cells. According to the results obtained, insulin receptor substrate 1 (IRS-1) expression was reduced by phycocyanin. Cell phenotype tests showed that siRNA knockdown of IRS-1 exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…HepG2 cells in the logarithmic growth stage were counted under the microscope, diluted to the concentration of 2000 cells/well, paved with 96‐well plates (100 µl), and cultured in an incubator for 24 h in DMEM medium supplemented with different concentrations of melanin (0,0.1, 0.2, 0.4, 0.6, 0.8, and 1 mg/ml). Then 10% CCK‐8 was added to each well, and the absorbance was measured at 450 nm and 650 nm by a microplate reader after incubation in the dark for 2 h [43]. Cell viability was calculated as follows: Cell viability=false[(AsAb)/(AcAb)false]×100%, <math display="block" altimg="urn:x-wiley:0233111X:media:jobm202100670:jobm202100670-math-0003" wiley:location="equation/jobm202100670-math-0003.png" xmlns="http://www.w3.org/1998/Math/MathML"><mrow><mrow><mi>Cell</mi><mo>\unicode{x02007}</mo><mi>viability</mi><mo>\unicode{x0003D}</mo><mo stretchy="false">[</mo><mrow><mo stretchy="false">(</mo><mrow><msub><mi mathvariant="normal">A</mi><mi>s</mi></msub><mo>\unicode{x02010}</mo><msub><mi mathvariant="normal">A</mi><mi>b</mi></msub></mrow><mo stretchy="false">)</mo><mo>/</mo><mo stretchy="false">(</mo><mrow><msub><mi mathvariant="normal">A</mi><mi>c</mi></msub><mo>\unicode{x02010}</mo><msub><mi mathvariant="normal">A</mi><mi>b</mi></msub></mrow><mo stretchy="false">)</mo></mrow><mo stretchy="false">]</mo><mo>\unicode{x000D7}</mo><mn>100</mn><mo>%</mo><mo>,</mo></mrow></mrow></math>where A S is the absorbance of the experimental hole (including cell, culture medium, CCK‐8 solution, and drug solution); A C is the absorbance of control well (including cells, culture medium, and CCK‐8 solution, excluding drugs); A b is the absorbance of blank hole (including culture medium and CCK‐8 solution, excluding cells and drugs).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…HepG2 cells in the logarithmic growth stage were counted under the microscope, diluted to the concentration of 2000 cells/well, paved with 96‐well plates (100 µl), and cultured in an incubator for 24 h in DMEM medium supplemented with different concentrations of melanin (0,0.1, 0.2, 0.4, 0.6, 0.8, and 1 mg/ml). Then 10% CCK‐8 was added to each well, and the absorbance was measured at 450 nm and 650 nm by a microplate reader after incubation in the dark for 2 h [43]. Cell viability was calculated as follows: Cell viability=false[(AsAb)/(AcAb)false]×100%, <math display="block" altimg="urn:x-wiley:0233111X:media:jobm202100670:jobm202100670-math-0003" wiley:location="equation/jobm202100670-math-0003.png" xmlns="http://www.w3.org/1998/Math/MathML"><mrow><mrow><mi>Cell</mi><mo>\unicode{x02007}</mo><mi>viability</mi><mo>\unicode{x0003D}</mo><mo stretchy="false">[</mo><mrow><mo stretchy="false">(</mo><mrow><msub><mi mathvariant="normal">A</mi><mi>s</mi></msub><mo>\unicode{x02010}</mo><msub><mi mathvariant="normal">A</mi><mi>b</mi></msub></mrow><mo stretchy="false">)</mo><mo>/</mo><mo stretchy="false">(</mo><mrow><msub><mi mathvariant="normal">A</mi><mi>c</mi></msub><mo>\unicode{x02010}</mo><msub><mi mathvariant="normal">A</mi><mi>b</mi></msub></mrow><mo stretchy="false">)</mo></mrow><mo stretchy="false">]</mo><mo>\unicode{x000D7}</mo><mn>100</mn><mo>%</mo><mo>,</mo></mrow></mrow></math>where A S is the absorbance of the experimental hole (including cell, culture medium, CCK‐8 solution, and drug solution); A C is the absorbance of control well (including cells, culture medium, and CCK‐8 solution, excluding drugs); A b is the absorbance of blank hole (including culture medium and CCK‐8 solution, excluding cells and drugs).…”
Section: Methodsmentioning
confidence: 99%
“…HepG2 cells in the logarithmic growth stage were counted under the microscope, diluted to the concentration of 2000 cells/well, paved with 96-well plates (100 µl), and cultured in an incubator for 24 h in DMEM medium supplemented with different concentrations of melanin (0,0.1, 0.2, 0.4, 0.6, 0.8, and 1 mg/ml). Then 10% CCK-8 was added to each well, and the absorbance was measured at 450 nm and 650 nm by a microplate reader after incubation in the dark for 2 h [43]. Cell viability was calculated as follows:…”
Section: Antitumor Activity Assaymentioning
confidence: 99%
“…( [3]) Although key to a good prognosis of HNSCC is early diagnosis and treatment [4], various factors also play a role in the prognosis of the patient. Due to the multifactorial pathogenesis of HNSCC, advanced stages of HNSCC are commonly associated with poor prognosis [5]. Therefore, identifying proteins and the mechanisms that are associated with metastasis and cancer progression can provide biomarkers for the prognosis and treatment targets for HNSCC.…”
Section: Introductionmentioning
confidence: 99%
“…IRS-1 and IRS-2 are widely expressed in humans and are, therefore, the most studied proteins in the family [ 3 ]. There is a relationship between IRS-1 and 2 and various types of cancer, such as breast [ 4 , 5 , 6 , 7 , 8 ], lung [ 9 ], prostate [ 10 ], hepatocarcinoma [ 11 , 12 , 13 ], neuroblastoma [ 14 , 15 ], head and neck [ 16 ], colorectal [ 17 , 18 ], esophageal squamous cell carcinoma [ 19 ], non-small cell lung cancer [ 20 ], and glioblastoma multiforme [ 21 ]. It has been observed that the expression and function of the IRS may vary in the different types of cancer.…”
Section: Introductionmentioning
confidence: 99%